Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00726-014-1675-5
|View full text |Cite
|
Sign up to set email alerts
|

l-Methionine supplementation maintains the integrity and barrier function of the small-intestinal mucosa in post-weaning piglets

Abstract: This study was conducted to test the hypothesis that different dietary Met levels affect small-intestinal mucosal integrity in post-weaning piglets. Two groups of piglets (n = 6/group) were weaned at 28 days of age and randomly allotted to a basal diet (without extra Met supplementation) or a Met-supplemented diet (with 0.12% L-Met) for 14 days. The standardized ileal digestible (SID) Met levels were 0.24 and 0.35%, respectively. At days 7 and 14 of the trial, venous blood samples were obtained from piglets, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 59 publications
7
70
0
2
Order By: Relevance
“…Stronger villus atrophy in the proximal than in the distal parts of the small intestine has also been observed by others [33,35]. However, Hamard et al [17,36] did not observe any intestinal atrophy in the proximal part of intestine in early-weaned piglets receiving a Thrlimiting diet during 2 weeks, but structural alterations might have occurred in an earlier time of the experiment.…”
Section: A More Affected Small Intestinal Architecture In Proximal Thmentioning
confidence: 56%
See 4 more Smart Citations
“…Stronger villus atrophy in the proximal than in the distal parts of the small intestine has also been observed by others [33,35]. However, Hamard et al [17,36] did not observe any intestinal atrophy in the proximal part of intestine in early-weaned piglets receiving a Thrlimiting diet during 2 weeks, but structural alterations might have occurred in an earlier time of the experiment.…”
Section: A More Affected Small Intestinal Architecture In Proximal Thmentioning
confidence: 56%
“…These findings suggest that TSAA may play a role in the control of intestinal growth and function by the regulation of the redox status. Moreover, the antioxidant and morphometric responses indicate that the proximal section of the gut is more affected than distal sections [33]. These authors also reported that the polyamine concentration is decreased more in the duodenum and jejunum than in the ileum when the Met supply is deficient.…”
Section: Glutathione System Changes In a Tissue-dependent Mannermentioning
confidence: 94%
See 3 more Smart Citations